2018
DOI: 10.1371/journal.pgen.1007178
|View full text |Cite
|
Sign up to set email alerts
|

Axin phosphorylation in both Wnt-off and Wnt-on states requires the tumor suppressor APC

Abstract: The aberrant activation of Wnt signal transduction initiates the development of 90% of colorectal cancers, the majority of which arise from inactivation of the tumor suppressor Adenomatous polyposis coli (APC). In the classical model for Wnt signaling, the primary role of APC is to act, together with the concentration-limiting scaffold protein Axin, in a “destruction complex” that directs the phosphorylation and consequent proteasomal degradation of the transcriptional activator β-catenin, thereby preventing s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 72 publications
(145 reference statements)
1
21
0
Order By: Relevance
“…APC may also act at the level of the Wnt receptor, inhibiting baseline activity in the absence of Wnt ligands by promoting clathrin-dependent receptor endocytosis (Saito-Diaz et al, 2018)-however, this role is only exhibited by certain APC family members. Another intriguing hypothesis is that APC can also promote Wnt signaling (Tacchelly-Benites et al, 2018;Takacs et al, 2008). Genetic studies in which the levels of both Drosophila APC proteins, APC1 and APC2, were manipulated in parallel revealed that reducing APC2 function attenuated activated Wnt signaling in fly eyes induced by the loss of APC1 (Takacs et al, 2008).…”
Section: Apc May Play Additional Positive and Negative Roles In Wnt Smentioning
confidence: 99%
See 1 more Smart Citation
“…APC may also act at the level of the Wnt receptor, inhibiting baseline activity in the absence of Wnt ligands by promoting clathrin-dependent receptor endocytosis (Saito-Diaz et al, 2018)-however, this role is only exhibited by certain APC family members. Another intriguing hypothesis is that APC can also promote Wnt signaling (Tacchelly-Benites et al, 2018;Takacs et al, 2008). Genetic studies in which the levels of both Drosophila APC proteins, APC1 and APC2, were manipulated in parallel revealed that reducing APC2 function attenuated activated Wnt signaling in fly eyes induced by the loss of APC1 (Takacs et al, 2008).…”
Section: Apc May Play Additional Positive and Negative Roles In Wnt Smentioning
confidence: 99%
“…Genetic studies in which the levels of both Drosophila APC proteins, APC1 and APC2, were manipulated in parallel revealed that reducing APC2 function attenuated activated Wnt signaling in fly eyes induced by the loss of APC1 (Takacs et al, 2008). The underlying mechanism was not fully defined, though effects on Axin stability and phosphorylation were suggested (Tacchelly-Benites et al, 2018;Takacs et al, 2008;Wang et al, 2016a). Interestingly, overexpressing APC2 in Drosophila embryos enhances accumulation of bCat only in Wnt-ON cells, supporting the idea that APC2 can aid in turning down destruction complex activity in response to Wnt signals (Schaefer et al, 2018).…”
Section: Apc May Play Additional Positive and Negative Roles In Wnt Smentioning
confidence: 99%
“…Similar to β-catenin, under basal conditions, Axin is phosphorylated by both GSK-3β and CKI [10,95,96] to function in the destruction complex and is subsequently dephosphorylated upon WNT pathway activation [10,97,98]. In updated regulation models, Axin phosphorylation occurs during both the 'off' and 'on' states of WNT signaling, and is dependent on another key destruction complex member, APC [99,100]. Another kinase that is reported to phosphorylate Axin is Cdk5 (Cyclin-dependent Kinase 5).…”
Section: Regulation Of Axin Functionsmentioning
confidence: 99%
“…In addition, axin participates in the LRP6 phosphorylation on the PPPSPxS motifs, which in turn cause the accumulation of axin in the destruction complex and then lead to the initiation of β-catenin signaling [71]. Recently, axin was found to be fully phosphorylated in the state of Wnt-off and partly phosphorylated in the state of Wnt-on mediated by GSK-3β [72].…”
Section: The Canonical Wnt Signaling Pathwaymentioning
confidence: 99%
“…APC may also serve as a positive regulator for Wnt signaling through downregulation of axin [77]. APC is vital for the phosphorylation of axin in both Wnt-off and Wnt-on states, the association with activated phospho-LRP6 and the rapid transition in axin activity [72]. Phosphorylated β-catenin requires APC for its targeting to ubiquitin ligase and protection from dephosphorylation mediated by protein phosphatase 2A (PP2A) [78].…”
Section: The Canonical Wnt Signaling Pathwaymentioning
confidence: 99%